Anticancer activity study of ethanol extract of Mahkota dewa fruit pulp (Phaleria macrocarpa (Scheff.) Boerl.) in C3H mouse mammary tumor induced by transplantation (Faculty of Medicine Universitas Indonesia, 2006)
The objective of this study is to investigate the anticancer activity of 70 % ethanol extract of Mahkota dewa fruit pulp Phaleria macrocarpa (Scheff.) Boerl. using C3H mouse mammary tumor induced by transplantation. Thirty two C3H mice were devided into 4 groups i.e. control and 3 groups of mice treated with ethanol extract of Mahkota dewa fruit pulp with the dose of 20, 40, and 80 fold human dose respectively, given orally by gastric tube after tumor transplantation for 30 days. Body weight and tumor volume measured twice a week. Tumor weight was measured after the animal was sacrificed, then fixed in formaldehyde for making histopathological preparation. The proliferation activity of tumor cells were examined by counting the AgNOR deposits detected after colloidal AgNOR staining. Apoptosis was assessed by mean of Tunel staining, and the width of necrotic area was identified by hematoxyllin eosin staining of the histological specimen. The results of the study showed that there were no statistical differences in tumor volumes, tumor weights, AGNOR values, and the necrotic area among control and the three treated groups (p>0,05), but apoptosis index significantly increased in the D3 (Mahkota dewa extract of eighty fold human dose) group (p<0,05). It was concluded that ethanol extract of Mahkota dewa fruit pulp at the dose of 20,40, and 80 fold human dose given orally after tumor transplantation for 30 days, did not inhibit the C3H mouse mammary tumor growth induced by transplantation, but the increased apoptosis was found in the group receiving ethanol extract of Mahkota dewa fruit pulp at the dose of 80 fold human dose. (Med J Indones 2006; 15:217-22)Keywords: Mahkota dewa, anticancer activity, proliferation, apoptosis